Peliosanthes linearifolia (Asparagaceae), a new species with linear leaves from Vietnam - Kroupsky, Ivan A.; Lyskov, Dmitry F.; Nguyen, Khang Sinh; Pham, Thoa Kim Thi; Nguyen, Cuong Huu; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Vislobokov, Nikolaynikolay A.; Tanaka, Noriyuki; Nuraliev, Maxim S. (Phytotaxa, 2023)
Peliosanthes linearifolia, a new species of Asparagaceae, is described and illustrated. The species was discovered in 2022 in Quang Nam Province, southern Vietnam. Peliosanthes linearifolia is remarkable for its linear to narrowly lanceolate leaves that are less than 1.3 cm wide. Such leaves were previously known only in P. graminea. Based on the floral characters of the new species, we assign it to the Peliosanthes teta species group. Peliosanthes linearifolia differs from P. teta, P. graminea and the other species of the group in the following combination of morphological traits: stoloniform rhizome, flowers solitary in axils of all primary bracts of inflorescence (i.e. inflorescence is a raceme), violet flowers and prominently lobed apex of the androecial corona.